Central centrifugal cicatricial alopecia - Blattner, Collin (Medknow Publications & Media Pvt Ltd, 2013)
Central centrifugal cicatricial alopecia is a common cause of progressive permanent apical alopecia. This unique form of alopecia includes entities previously know as “hot comb alopecia,” “follicular degeneration syndrome,” “pseudopelade” in African Americans and “central elliptical pseudopelade” in Caucasians. The etiology appears to be multifactorial and the condition occurs in all races.